PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN RUMAH SAKIT BHAYANGKARA TK I PUSDOKKES POLRI - Marifah Hidayati; Edy Sanusi Silitonga (Jurnal Ekonomi dan Industri, 2025)
The analyze the influence of work environment and work discipline on employee performance at Rumah Sakit Bhayangkara Tk. 1 Pusdokkes Polri. This research is included in the category of causal associative research using a quantitative approach. The population in this study were employees of Rumah Sakit Bhayangkara Tk. 1 Pusdokkes Polri. The sampling technique uses simple random sampling technique. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the work environment and work discipline have a positive and significant on employee performance at Rumah Sakit Bhayangkara Tk. 1 Pusdokkes Polri.